Wind-powered locomotion mechanism for a wandering robot exploring Titan - Kurian, Sam; Upadhyay, Saurabh (Cranfield University, 2026)
This paper proposes a wind-powered locomotion mechanism design for wandering robots on Titan, WANDER-Bot. Existing planetary robots use a substantial amount of their power budget for locomotion. Typical power sources include RTGs and solar cells, which experience performance degradation in their power output over time, and are not suitable for replacement or repair. Composed of a Savonius wind turbine mechanism, reduction gearbox mechanism, and Jansen linkage walking mechanism, the proposed wandering robot locomotion design addresses these limitations by using wind energy, and simple mechanical links designed with consideration of ISRU manufacturing. The WANDER-Bot lab prototype takes a low-cost, low-storage, low-power approach to the design and locomotion. Performance analysis is conducted on the robot components in replicated Titan conditions.
© The Authors
Keywords: Planetary robotics; Rover; space exploration; Titan exploration; Jansen mechanism; Titan; Planetary exploration; Savonius wind turbine; low-cost; ISRU